ANALISA RASIO LAPORAN KEUANGAN UNTUK MENILAI KINERJA PERUSAHAAN PT SEMEN INDONESIA TBK (PERSERO) - Erica, Denny (www.bsi.ac.id, 2017)
As one of the state-owned companies engaged in cement industry which was established on August 7, 1957, PT Semen Indonesia (Persero) Tbk, has a financial statement that must always be analyzed periodically from one period to the next that can be used as very basic information useful for internal and external companies. In this case the company can use ratio analysis to the financial statements. While for data collection method used in this research use observation method and library study related to financial data of PT Semen Indonesia (Persero) Tbk, to then be analyzed by calculating arithmetic ratio which can be interpreted in economic relation related to company performance. The result of financial statement analysis by using measurement of Liquidity Ratio, Leverage Ratio, Activity Ratio, Profitability Ratio, and can be said company in good condition.Keywords: Company performance, financial ratio analysis